Contestations of Women's Body Autonomy on TikTok: A Study of Ideology, Qur'anic Interpretation, and Gender Identity among Indonesian Islamic Organizations - Nurani, Shinta; Maulana, Luthfi; Marom, Naelil (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2025)
This study analyses contestations over women’s body autonomy on social media among four Indonesian Islamic organisations: Nahdlatul Ulama (NU), Muhammadiyah, the Indonesian Ulema Council (MUI), and Salafi groups. Using Michel Foucault’s theory of power, data from interviews and documentary studies reveal three key findings. First, conceptions of women’s body autonomy vary considerably—from traditionalist to neo-modernist within NU, classical revivalist to reformist in Muhammadiyah, monolithic among Salafi groups, and contextual in MUI. Second, interpretations of QS. An-Nur: 31 regarding aurat constitute the primary point of divergence. Third, a notable shift in gender identity emerges, particularly among Neo-Modernist NU and Reformist Muhammadiyah, who actively challenge traditional stigmas. This study illuminates how religious ideology mediates global media influences on local gender politics in Indonesia.